Management of lower eyelid laxity with pressure using conformer and custom ocular prosthesis - Aidilla, Dara; Ariyani; Z Tamin, Haslinda (Indonesian Journal of Prosthodontic, 2024)
Background: One of the successes in making an ocular prosthesis is sufficient eye socket condition, so post-enucleated patient treatment with lower eyelid laxity is a challenge for prosthodontists due to its difficulty in obtaining the retention of an ocular prosthesis. Long-term use of an ill-fitting ocular prosthesis will cause lower eyelid laxity and irritation due to the movement of the prosthesis that is insubordinate with the eye muscles when it is functioning. Objectives: This paper represents the management of lower eyelid laxity in a post-enucleated patient with pressure using conformer and custom ocular prosthesis. Case Report: A twenty-year-old female patient came to Dental Hospital Universitas Sumatera Utara with a red, swollen, and frequent discharge from the eye socket. The custom ocular prosthesis used by the patient often falls out of the socket and she requests a new custom ocular prosthesis. The patient was referred to an ophthalmologist for irritated socket. Then, a definitive impression is made. Two sclera waxes were fabricated in a definitive cast to obtain a conformer and custom ocular prosthesis. Conformer was worn for three weeks to ensure an adequate lower eyelid. Then, a new custom ocular prosthesis was inserted into the socket. Pressing the conformer towards the lower eyelid will stimulate and train the eyelid muscles to move and prevent atrophy, so it can restore the support of the lower eyelid. Conclusion: Lower eyelid laxity can be corrected with a pressure-assisted conformer, resulting in a functionally and aesthetically pleasing custom ocular prosthesis. Keywords: conformer, ocular prosthesis, lower eyelid laxity